Ressources non renouvelables et taxation - Gaudet, Gérard (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractA discussion of the main controversies over the tax treatment of the natural resource industries, of optimal taxation in relation to various policy objectives, and of the possibility of attaining these objectives through the main forms of taxation and royalties now in existence.